Complete blood count and biochemistry reference intervals for giant anteaters (Myrmecophaga tridactyla) cubs - Juliana D. Silveira; Juliana M.M. Silva; Erika P.T. Teixeira; Rafael F. Barros; Victor G. Castro; Maísa P. Rios; João H.F.F. Naves; Arnaud L.J. Desbiez; Líria Q.L. Hirano (Pesquisa Veterinária Brasileira)
ABSTRACT: The giant anteater (Myrmecophaga tridactyla) is a large and threatened neotropical mammal, with a high number of rescued orphans kept in captivity for parental care. There is a lack of information about laboratory reference intervals (RIs) of giant anteater cubs. The purpose of this study was to establish laboratory RIs of 25 healthy giant anteater cubs from the Brazilian Cerrado, and to assess whether sex influence laboratory results. Between sexes, the values that showed significant differences were packed cell volume (p-value = 0.0306) and relative eosinophils (p-value = 0.0445), with higher means for males. The biochemistry data from the present study were compared with previous studies. Globulin, alanine transaminase, cholesterol, alkaline phosphatase, calcium, direct and total bilirubin showed higher values in cubs than in adults. This paper seems to be the first published study RIs for giant anteater cubs and highlights the importance of more veterinary research with comparative aspects between animals of different sexes and ages.